(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the concept of the ideal hero and emphasizes the theoretical dimensions of the representational means that have been shaped throughout the development of Uzbek novelistics. It reveals the underlying causes behind the manifestation of an individual’s complex psychological experiences within the nature of the novel.